PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Astuti Astuti; Lovy Herayanti; Intan Kusuma Wardani (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
The study aims to find out the influence of 'take and give' learning models on vector subjects. The sample used as a control class was 32 students of class X MIPA 2 and 32 students of class X MIPA 3 as an experiment class. Data collection using pre-test and post-test consisting of 8 essay questions and analyzed using t-test. The results show that the t-test value is lower than the t-table. The study concluded that the 'take and give' learning model had a positive effect on student learning outcomes at SMA Negeri 1 Madapangga in the 2018/2019 school year.